PENGARUH KINERJA EKONOMI MAKRO TERHADAP NILAI TUKAR PETANI - Azhar Bafada (Quantitative Economics Journal, 2014)
This study aims to analyze the effect of macroeconomic performance, i.e., the inflation and gross regional domesticproduct of agriculture sector (PDRB), on thefarmer’s term of trade (NTP) in Southeast Sulawesi. Data used are of quarterly, covering 2006-2012. The analysis is undertaken by using a multiple linear regression withordinary least squaresestimation method(OLS). The results showed that the inflation has a significant effecton the farmer’s term oftrade. Theeffect of the inflation on the farmer’s term of trade is responsive, the inflation of 1% will be able to decrease thefarmer’s term of trade at 1.61 %. Agricultural SectorPDRB does not significant affecton thefarmer’s term of trade. This study implies that the inflation control is an important task for the government so that the effect of inflation does not result in a sharp decrease in NTP.